2018
DOI: 10.1007/s11239-018-1626-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for acute kidney injury in patients with excessive anticoagulation on warfarin: a retrospective study

Abstract: Anticoagulant-related nephropathy is an acute kidney injury (AKI) associated with excessive anticoagulation. The nature of the association between excessive anticoagulation with warfarin and AKI and its incidence remain unclear. To evaluate the incidence of AKI in excessively anticoagulated patients taking warfarin and examine potential risk factors. A retrospective chart review was performed in patients on chronic warfarin. The primary outcome was AKI, defined as an acute increase in creatinine of > 26.5 µmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Since 2009, several studies have confirmed the hypothesis proposed by Brodsky that excessive anticoagulation is associated with WRN [56][57][58][59]. Golbin et al described the largest biopsy-proven case series of AKI induced by other VKAs, specifically the first cases of AKI by fluindione and acenocoumarol [60].…”
Section: Anticoagulant-related Nephropathy and Progression Of Kidney mentioning
confidence: 87%
“…Since 2009, several studies have confirmed the hypothesis proposed by Brodsky that excessive anticoagulation is associated with WRN [56][57][58][59]. Golbin et al described the largest biopsy-proven case series of AKI induced by other VKAs, specifically the first cases of AKI by fluindione and acenocoumarol [60].…”
Section: Anticoagulant-related Nephropathy and Progression Of Kidney mentioning
confidence: 87%
“…118 Although not initially widely accepted, the association between anticoagulation and AKI has been confirmed in several additional studies and may be more common than initially thought. [119][120][121] For example, in 1 retrospective nonbiopsy study, 20.5% of patients treated with warfarin with a first INR of >3 developed AKI within 1 week; those with AKI had a 65% increased risk of mortality within 1 year. 122 Risk factors for anticoagulant-related nephropathy include CKD, older age, diabetes mellitus, hypertension, and cardiovascular disease.…”
Section: Special Considerations Anticoagulant-related Nephropathymentioning
confidence: 99%
“…Accordingly, the term "anticoagulant-related nephropathy" (ARN) is preferred. Since the seminal report of pathologic features of warfarin-related nephropathy, 1 several investigators published case reports and retrospective studies showing AKI in association with different anticoagulants, including multiple case reports and case series that describe warfarin-related nephropathy, [7][8][9][10][11][12] case reports of dabigatran-associated AKI, [13][14][15][16][17] a case report of AKI in a patient with thrombocytopenia, 18 and a case of biopsy-proven ARN in a patient receiving antiplatelet medications. 19 Given the existing data for this newly described entity and the presence of multiple causes for anticoagulation, we explored our database of existing kidney biopsies since our initial description of ARN to describe ARN with additional details, including agents that may predispose to this unusual cause of AKI.…”
mentioning
confidence: 99%
“…Accordingly, the term “anticoagulant-related nephropathy” (ARN) is preferred. Since the seminal report of pathologic features of warfarin-related nephropathy, 1 several investigators published case reports and retrospective studies showing AKI in association with different anticoagulants, including multiple case reports and case series that describe warfarin-related nephropathy, 7 , 8 , 9 , 10 , 11 , 12 case reports of dabigatran-associated AKI, 13 , 14 , 15 , 16 , 17 a case report of AKI in a patient with thrombocytopenia, 18 and a case of biopsy-proven ARN in a patient receiving antiplatelet medications. 19…”
mentioning
confidence: 99%